2010
DOI: 10.1002/dys.400
|View full text |Cite
|
Sign up to set email alerts
|

Do children with developmental dyslexia have impairments in implicit learning?

Abstract: We explored implicit learning in a group of typically developing and developmental dyslexic primary school children (9-12 y) using a modified artificial grammar learning task. Performance was calculated using two measures of performance: a perfect free recall (PFR) score and a grammaticality judgment score. Both groups of children required the same amount of exposure to memorize the items (i.e. PFR performance) (t((30))=1.620, p>0.05; p-value reported two-tailed). However, repeated measures ANOVA (Participant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
5
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 56 publications
(101 reference statements)
5
41
5
1
Order By: Relevance
“…Memory for order is thus critical for performance in this task and it seems that, at least partly, similar orderlearning mechanisms underlie performance in the Hebb repetition task and the SRT tasks (Page et al, 2006). In line with the SOLID hypothesis, a majority of studies using the SRT paradigm have reported impaired implicit-sequence-learning abilities in individuals with dyslexia (see Lum et al, 2013 for a recent meta-analysis and Pavlidou et al, 2010, for converging evidence in artificial grammar learning). Serial-order learning in dyslexia One fundamental characteristic of most serial-order learning tasks is that they proceed over a relatively extended time period (Hedenius et al, 2013), tapping into the transfer between short and long-term memory.…”
Section: Dyslexia As a Dis-order?mentioning
confidence: 87%
See 1 more Smart Citation
“…Memory for order is thus critical for performance in this task and it seems that, at least partly, similar orderlearning mechanisms underlie performance in the Hebb repetition task and the SRT tasks (Page et al, 2006). In line with the SOLID hypothesis, a majority of studies using the SRT paradigm have reported impaired implicit-sequence-learning abilities in individuals with dyslexia (see Lum et al, 2013 for a recent meta-analysis and Pavlidou et al, 2010, for converging evidence in artificial grammar learning). Serial-order learning in dyslexia One fundamental characteristic of most serial-order learning tasks is that they proceed over a relatively extended time period (Hedenius et al, 2013), tapping into the transfer between short and long-term memory.…”
Section: Dyslexia As a Dis-order?mentioning
confidence: 87%
“…Although the above definition focuses on problems with reading and spelling, the literature on dyslexia reveals a strikingly broad scope of associated nonlinguistic dysfunctions. Examples include impaired short-term memory (e.g., Martinez Perez, Majerus, Mahot & Poncelet, 2012a), working memory (e.g., Gathercole, Alloway, Willis, & Adams, 2006;Smith-Spark & Fisk, 2007), implicit (sequence) learning (e.g., Lum, Ullman, & Conti-Ramsden, 2013;Pavlidou, Kelly, & Williams, 2010;Vicari, Marotta, Menghini, Molinari, & Petrosini, 2003), motor functions (e.g., Nicolson, Fawcett, & Dean, 2001) and sensory functioning (e.g., Stein, 2001, but see also Goswami, 2015). …”
Section: Dyslexiamentioning
confidence: 99%
“…However, these groups also show learning impairments in non-motor paradigms. Both children with dyslexia [10] and adults with SLI 11, 12 appear to have difficulty extracting structure from novel sequences in artificial grammar learning (AGL) paradigms. These difficulties in making judgements about grammaticality are not related to problems holding information in mind because deficits are present even when children with dyslexia can accurately recall a training sequence from memory 10, 13.…”
Section: What Learning Impairments Are Observed In Developmental Langmentioning
confidence: 99%
“…Both children with dyslexia [10] and adults with SLI 11, 12 appear to have difficulty extracting structure from novel sequences in artificial grammar learning (AGL) paradigms. These difficulties in making judgements about grammaticality are not related to problems holding information in mind because deficits are present even when children with dyslexia can accurately recall a training sequence from memory 10, 13. Other studies have found that children with SLI perform worse than typically developing peers at extracting regularities from speech streams in statistical learning paradigms [14], although they can extract relevant information when exposure is doubled [15].…”
Section: What Learning Impairments Are Observed In Developmental Langmentioning
confidence: 99%
“…Pattern obtained from the testing phase revealed that children with dyslexia despite have been linked to short-term memory deficits [18]; it seems they were able to explore the courseware as instructed. Although at first they looked confused, after a while most of them were excited to explore the courseware by themselves.…”
Section: Resultsmentioning
confidence: 98%